Household food waste and food security: a review of behavioral, socioeconomic, and educational determinants - Aisy, Nabilah Rihadatul; Rahmawati, Widya; Rahmawati, Irma Sarita (Universitas Gadjah Mada, 2025)
Purpose: This systematic review examines the relationship between household food waste and food security, exploring key behavioral, socio- economic, and educational determinants that shape this interconnection in domestic settings. Methods: The review adhered to PRISMA guidelines and applied Covidence software to screen items obtained from Scopus, Pub- Med, and Web of Science, from 2015 to 2025. Search terms used included